Justice For All In Mediation: What The Pandemic, Racial Justice Movement, And The Recognition Of Structural Racism Call Us To Do As Mediators - Isabelle R. Gunning (Washington University Journal of Law and Policy, 2022)
There is no question that the COVID-19 pandemic has disparately impacted poor and Black communities—with those communities experiencing higher rates of infection and serious health complications, including death. Recent events have served as a catalyst to a “racial reckoning” in public discourse and a call on individuals and institutions to identify and address systemic racism. In this Article, the author argues that the dispute resolution community should take a special role in this time of renewed interest in, and urgency around, conversations related to race. Gunning argues that the dispute resolution community must acknowledge that the presence of racism and its negative impacts are embedded in the very structures of the mediation processes the field utilizes. Gunning concludes by advocating for a commitment to the transformation of dispute resolution processes by using a robust and contemporary view of “restorative justice” that demands looking at justice at both the individual and societal levels.
Keywords: Black Communities; COVID-19 Pandemic; Systemic Racism; Dispute Resolution; Mediation; Structural Racism; Restorative Justice